Patient-derived tumor xenograft models established from samples obtained by endobronchial ultrasound-guided transbronchial needle aspiration. Issue 2 (August 2015) - Nakajima, Takahiro; Geddie, William; Anayama, Takashi; Ko, Hyang Mi; da Cunha Santos, Gilda; Boerner, Scott; Wang, Tao; Wang, Yu-hui; Li, Ming; Pham, Nhu-An; Tsao, Ming Sound; Yasufuku, Kazuhiro
Highlights: We established patient derived tumor xenograft murine models using EBUS-TBNA samples. 42.1% (8/19) of patients' samples engrafted in the immune deficient mice. There was no correlation with blood/lymphocyte contamination or degree of necrosis. The histological characters of each sample were well maintained in the each passage. Abstract: Objectives: There has been limited utility for laboratory tumor models to predict clinical performance of cancer drugs. Clinical drug trials usually recruit patients that have advanced disease, therefore preclinical tumor models that closely reflect this characteristic will be more reliable to test candidate drugs. We evaluated the use of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) to sample metastatic lymph nodes in patients to establish patient-derived tumorxenograft (PDX) models of advanced lung cancer. Materials and methods: Cell suspensions from TBNA aspirates were implanted into the subcutaneous tissue of NSG (NOD scid) gamma) mice. The success rate of PDX establishment was associated with tumor histopathology and the cellularity and cytopathological diagnosis of the primary EBUS-TBNA samples. Results: From December 2011 to June 2012, 19 patients were enrolled in this study. Successful engraftment was achieved in 8/19 cases (42.1%). The duration between inoculation and tumor formation averaged 62.4 days (13–144 days). The engrafted tumors included 3 adenocarcinomas (3/12: 25%), 2 squamous cell carcinomas (2/3: 67%), 1 large cell carcinoma (1/1: 100%), and 2 small cell carcinomas (2/3: 67%). Conclusion: EBUS-TBNA samples can be used for establishment of tumor xenograft model in immunodeficient mice.